Analisis Kepuasan dan Kepercayaan Pengunjung Agrowisata Edukasi Sentulfresh - Lainatussifa Lainatussifa; Wahyu Budi Priatna; Heny Kuswanti Suwarsinah (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
Changes in the children's learning curriculum that emphasize children's activities and experiences not just reading material, making agro-tourism an alternative learning media for interaction that is chosen by the school. As one of the agro-education objects, Sentulfresh needs always to evaluate their performance of the marketing mix (product, price, place, promotion, people, process and physical evidence) through visitor satisfaction and trust. This study aims to analyze any marketing mix variables that affect the satisfaction variable, is there effect of satisfaction on trust and where is the satisfaction level of Sentulfresh visitors. Data collection was carried out on 70 respondents who had visited Sentulfresh. The data analysis method used were the Structural Equation Model Partial Least Square (SEM PLS) and the Customer Satisfaction Index (CSI). SEM-PLS analysis results show that all marketing mix variables have no significant effect on visitor satisfaction, while satisfaction has a significant effect on visitor trust. CSI analysis results shows that Sentulfresh visitor satisfaction is at the “satisfied” level.